Активізація навчально-пізнавальної діяльності майбутніх інженерів-педагогів за допомогою ділових ігор - Штефан, Людмила Володимирівна (НТУ "ХПІ", 2012)
The article discusses the business games as a means of enhancing learning. Stages of business games and their application in higher engineering and pedagogical educational establishment.
Keywords: професійна підготовка; конкурентоздатність; інженер-педагог; ділова гра